Atopobium and Fusobacterium as novel candidates for sarcoidosis-associated microbiota. Issue 6 (14th December 2017) - Zimmermann, Alexandra; Knecht, Henrik; Häsler, Robert; Zissel, Gernot; Gaede, Karoline I.; Hofmann, Sylvia; Nebel, Almut; Müller-Quernheim, Joachim; Schreiber, Stefan; Fischer, Annegret
Sarcoidosis is a granulomatous disease that mainly affects the lung. A role of microbial factors in disease pathogenesis is assumed, but has not been investigated systematically in a large cohort. This cross-sectional study compared the lung microbiota of 71 patients with sarcoidosis, 15 patients with idiopathic pulmonary fibrosis (non-infectious controls) and 10 healthy controls (HCs). Next-generation sequencing of 16S DNA was used on bronchoalveolar lavage samples to characterise the microbial composition, which was analysed for diversity and indicator species. Host genotypes for 13 known sarcoidosis risk variants were determined and correlated with microbial parameters. The microbial composition differed significantly between sarcoidosis and HC samples (redundancy analysis ANOVA, p=0.025) and between radiographic Scadding types. Atopobium spp. was detected in 68% of sarcoidosis samples, but not in HC samples. Fusobacterium spp. was significantly more abundant in sarcoidosis samples compared with those from HCs. Mycobacteria were found in two of 71 sarcoidosis samples. Host-genotype analysis revealed an association of the rs2076530 ( BTNL2 ) risk allele with a decrease in bacterial burden (p=0.002). Our results indicate Scadding type-dependent microbiota in sarcoidosis BAL samples. Atopobium spp. and Fusobacterium spp. were identified as sarcoidosis-associated bacteria, which may enable new insights into the pathogenesis and treatment of the disease. Sarcoidosis lung microbial profiles http://ow.ly/IfTC30gxm2U